2020
DOI: 10.3389/fchem.2020.587456
|View full text |Cite
|
Sign up to set email alerts
|

Selective Biosynthesis of Furoic Acid From Furfural by Pseudomonas Putida and Identification of Molybdate Transporter Involvement in Furfural Oxidation

Abstract: Upgrading of furanic aldehydes to their corresponding furancarboxylic acids has received considerable interest recently. Herein we reported selective oxidation of furfural (FAL) to furoic acid (FA) with quantitative yield using whole-cells of Pseudomonas putida KT2440. The biocatalytic capacity could be substantially promoted through adding 5-hydroxymethylfurfural into media at the middle exponential growth phase. The reaction pH and cell dosage had notable impacts on both FA titer and selectivity. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…It should be noted that the ped cluster encoding the above-mentioned dehydrogenases is not well conserved among Pseudomonads, and strains like P. taiwanensis VLB120 completely lack the cluster (pseudomonas.com [94]). However, Pseudomonads have a large repertoire of other dehydrogenases, and recent studies point to the involvement of, e.g., molybdenum-dependent enzymes [95][96][97].…”
Section: Dealing With the Toxicant: Detoxification And Damage Recoverymentioning
confidence: 99%
“…It should be noted that the ped cluster encoding the above-mentioned dehydrogenases is not well conserved among Pseudomonads, and strains like P. taiwanensis VLB120 completely lack the cluster (pseudomonas.com [94]). However, Pseudomonads have a large repertoire of other dehydrogenases, and recent studies point to the involvement of, e.g., molybdenum-dependent enzymes [95][96][97].…”
Section: Dealing With the Toxicant: Detoxification And Damage Recoverymentioning
confidence: 99%
“…The construction of gcd and gtsABCD mutants was conducted as described in our previous study [ 43 ]. Specifically, genomic DNA of P. putida KT2440 was isolated using a Bacteria Genomic DNA Extraction Kit (Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…102 Ouyang and co-workers evaluated the ability of P. putida KT2440 (also deposited as DSM 6125 and ATCC 47054) to oxidize HMF and furfural. 103,104 This strain was able to smoothly convert around 2, entry 13). The authors identified a Mo-containing transporter from this microorganism that is involved in the oxidation of the furans.…”
Section: Whole-cell Catalysismentioning
confidence: 97%
“…P. putida is an important industrial microorganism because of its versatile metabolism and low nutritional requirements as well as the high robustness against extreme environmental conditions such as extreme pH and tolerance to toxic chemicals and solvents . Ouyang and co-workers evaluated the ability of P. putida KT2440 (also deposited as DSM 6125 and ATCC 47054) to oxidize HMF and furfural. , This strain was able to smoothly convert around 170 mM of furans to the target carboxylic acids, with almost quantitative yields (Table , entry 13). The authors identified a Mo-containing transporter from this microorganism that is involved in the oxidation of the furans .…”
Section: Catalytic Oxidationmentioning
confidence: 99%
See 1 more Smart Citation